Electrospun Filaments Embedding Bioactive Glass Particles with Ion Release and Enhanced Mineralization - Serio, Francesca; Miola, Marta; Verne, Enrica; Pisignano, Dario; Boccaccini, Aldo R.; Liverani, Liliana (Nanomaterials, 2019)
Efforts in tissue engineering aim at creating scaffolds that mimic the physiological environment with its structural, topographical and mechanical properties for restoring the function of damaged tissue. In this study we introduce composite fibres made by a biodegradable poly(lactic acid) (PLLA) matrix embedding bioactive silica-based glass particles (SBA2). Electrospinning is performed to achieve porous PLLA filaments with uniform dispersion of bioactive glass powder. The obtained composite fibres show in aligned arrays significantly increased elastic modulus compared with that of neat polymer fibres during uniaxial tensile stress. Additionally, the SBA2 bioactivity is preserved upon encapsulation as highlighted by the promoted deposition of hydroxycarbonate apatite (HCA) upon immersion in simulated body fluid solutions. HCA formation is sequential to earlier processes of polymer erosion and ion release leading to acidification of the surrounding solution environment. These findings suggest PLLA-SBA2 fibres as a composite, multifunctional system which might be appealing for both bone and soft tissue engineering applications.
CRIS-Team WoS Importer:2019-03-29